2009
DOI: 10.1177/1049909109341867
|View full text |Cite
|
Sign up to set email alerts
|

How to Attract More Males to Community-Based Hospice Palliative Care Volunteer Programs

Abstract: Two separate studies were conducted to better understand why so few middle-aged and older men volunteer in hospice palliative care; only about 10% of the patient/family care volunteers in New Brunswick's community-based hospice palliative care volunteer programs are men. In study 1, 15 (22%) of the 68 men who read a brief description about the kinds of things that hospice palliative care volunteers do expressed an interest in this type of volunteerism. The main reasons given for their lack of interest included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 13 publications
4
16
0
Order By: Relevance
“…It is well known that much more women are engaged in hospice/palliative care volunteer programs than men [5]. This assumption is confirmed by the authors in their recent study showing that significantly more women than men were interested in this kind of volunteer experience, whereas men, in general in Canada seem to volunteer on similar levels as women.…”
Section: Different Motivations Of Male Volunteers In Hospice Palliatimentioning
confidence: 65%
See 1 more Smart Citation
“…It is well known that much more women are engaged in hospice/palliative care volunteer programs than men [5]. This assumption is confirmed by the authors in their recent study showing that significantly more women than men were interested in this kind of volunteer experience, whereas men, in general in Canada seem to volunteer on similar levels as women.…”
Section: Different Motivations Of Male Volunteers In Hospice Palliatimentioning
confidence: 65%
“…This assumption is confirmed by the authors in their recent study showing that significantly more women than men were interested in this kind of volunteer experience, whereas men, in general in Canada seem to volunteer on similar levels as women. The authors of this study [5] suggest that, in order to attract male volunteers, a special 'job description', including the tasks they would like to perform, should be established. Of those men who vocalized an interest in volunteering in hospice or palliative care, the desire to help was a common motivation.…”
Section: Different Motivations Of Male Volunteers In Hospice Palliatimentioning
confidence: 99%
“…In 2 studies, Claxton-Oldfield and colleagues investigated why relatively few men volunteer for hospice palliative care. 3 In their studies of middle-aged and older men, less than a quarter expressed an interest in hospice palliative care volunteerism after reading a brief description of typical volunteer tasks although 80% indicated that they knew about hospice palliative care (study 1). The few men who reported some interest in hospice palliative care volunteerism reported altruistic and humanitarian motives ("I see the need or enjoy helping others"), existing similar volunteer activities ("I already do this kind of work"), and/or self-serving motives ("I might need help myself or would like help for my family").…”
Section: The Functional Approach To Motivationmentioning
confidence: 99%
“…In study 2, participants were asked to choose from a list of tasks the ones that they could imagine themselves performing as hospice volunteers. 3 Males chose most of the social (eg, talk to the patient), practical (eg, drive the patient to the doctor), and emotional support tasks (eg, listening to a patient's life story) and were less interested in administrative tasks (eg, work in the volunteer program's office), tasks that involve direct hands on (physical) patient care/contact (eg, help with feeding), and tasks involving provision of grief and bereavement support. Kolnick and Mulder 13 conducted focus groups with males in order to develop effective recruitment strategies for male volunteers in a care context.…”
Section: The Functional Approach To Motivationmentioning
confidence: 99%
See 1 more Smart Citation